Вітростійкість окремих складових елементів декоративних насаджень як функція їх способу вирощування - Doroshenko, O.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
Calculations of single tree wind-resistance were shown. Single trees were grown in different ways: individually and in group, but the first method is advantage. According to the results obtained temporary growing of single trees together with trees of fourth size and shrubs or only with shrubs was recommended.